Absenteeism, childcare and the effectiveness of pension reforms - Flavia Coda Moscarola; Elsa Fornero; Steinar Strøm (IZA Journal of European Labor Studies, 2016)
Both economic and epidemiological literature have shown that perceived high strain at work and lack of social infrastructures are good predictors of sick leave. The latter is particularly relevant in countries where facilities for children and care services are scarce and women are asked to fill the gap. The Italian 2011 pension reform significantly restricted age and seniority requirements for retirement, especially for women in private employment. We investigated whether older Italian employed women reacted to the postponement of retirement by increasing their sick leave. The empirical analysis offers unequivocal evidence that this has indeed been the case, in particular, for low-income grandmothers living in regions with a poor supply of childcare services. Radical reforms risk losing some of their effectiveness if they are not accompanied by parallel measures designed to introduce the welfare provisions previously indirectly and inadequately provided by the pension system, such as care facilities.
Keywords: J26; J13; C33; 330; Pension reform; Sick leave; Childcare